QUALITY EVALUATION OF ASPECTS OF PLANNING APPLICATION PBM, ASPECTS OF HUMAN RESOURCES AND ORGANIZATIONAL ASPECTS IN JURUSAN/PRODI POLTEKKES KEMENKES KUPANG TAHUN 2011 - RAGU HARMING KRISTINA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2013)
Background: Quality of the learning process can be said to be good if successfully change attitudes, behaviors and skills of learners in accordance with the purpose of education. So that the learning process can be done well and achieved the standard of competence that is expected, required a Learning Process Standards for educational institutions that includes planning, implementation, assessment and monitoring. Purpose: Get an overview of the application of quality standards on aspects of PBM Planning, Human Resources and Organization in Jurusan/Prodi Poltekkes Kemenkes Kupang. Research Methodology: This research is a descriptive study, the design (design) evaluative study of the retrospective observational nature. Population in this research is the program manager in the Jurusan/ Prodi Politeknik Kesehatan Kemenkes Kupang consists of Kajur/Kaprodi, Sekjur/Sekprodi, responsible person in charge of academic and student affairs. The total population of 36 people (N = 36) consisted of: Kupang Nursing, Midwifery, Environmental Health, Pharmacy, Dental Nursing, Nutrition, Health Analyst, Prodi Nursing Ende and Waingapu, each four (4) people per Department/Prodi. The experiment was conducted for three months, ie May to July 2011. The data were processed and analyzed using descriptive analysis. Aspects studied/unit of analysis is the planning aspect of PBM, HR and organizational aspects, aspects of student. Results: PBM planning, HR is not in accordance with the defined quality standards polytechnic MoH Kupang, Application of the organizational structure as well as the accessories according Ortal MOH guidelines, Documenting HR file has not all been well documented, not all lecturers Placement qualification standards lecturer, lecturer to student ratio is still not according to the standard. Suggestion: Need good planning to PBM and human resources in the Ministry of Health polytechnic Kupang so as to achieve the expected quality standards. Need a good organization to document all relevant files the learning process so as to achieve quality standards that have been set.